Prevalance of Sepsis in Chronic Hemodialysis Patients and its Management - Zia , Waqar; Rafiq Abbasi, Muhammad Sajid; Muhammad Jawad; Shah, Muhammad Afnan Ullah; Asmat Ullah; Shahzadi, Kiran (Indus Journal of Bioscience Research, 2025)
Background: Sepsis is a major cause of morbidity and mortality in patients undergoing maintenance hemodialysis due to repeated vascular access, impaired immune function, and frequent healthcare exposure. Understanding the prevalence, microbial spectrum, and antibiotic sensitivity patterns of sepsis in this population is essential for improving infection control and treatment outcomes. Objectives of this study are to determine the frequency of sepsis in patients undergoing chronic hemodialysis and to identify the common causative organisms along with their antibiotic sensitivity patterns. Methods: This descriptive cross-sectional study was conducted in the Department of Nephrology at Pakistan Institute of Medical Sciences (PIMS) from May to December 2024. Non-probability consecutive sampling technique was employed to select 165 patients who were aged 18 to 65 years who were on maintenance hemodialysis. Sepsis was diagnosed using Sequential Organ Failure Assessment (SOFA) criteria in the presence of infection along with Systemic Inflammatory Response Syndrome (SIRS), qSOFA score, and serum lactate levels. Microbiological analysis of blood cultures was done on periphery veins and central veins catheters. Standard microbiological identification was done, and testing of antibiotic susceptibility was done as per the Clinical and Laboratory Standards Institute (CLSI) 2022 guidelines. The SPSS version 25 was used to analyze the data. Results: Among 165 hemodialysis patients, the mean age was 41.55 ± 13.63 years. Sepsis was identified in 46 patients, yielding a prevalence of 27.9%. Staphylococcus species were the most frequently isolated organisms (52.2%), followed by gram-negative bacteria (30.4%) and Streptococcus species (17.4%). Imipenem (63.0%) and vancomycin (54.3%) showed the highest antibiotic sensitivity, whereas cephazolin (10.9%) and ceftriaxone (13.0%) showed low sensitivity. Methicillin resistance was observed in 65.2% of isolates. A significant association was found between CKD Stage 5 and sepsis (p = 0.038). Conclusion: Sepsis is a frequent complication in patients receiving maintenance hemodialysis, mostly with gram-positive pathogens. The high level of antimicrobial resistance underlines the role of the prevention of infections and local antibiogram to implement the most effective empirical treatment.